2020
DOI: 10.1159/000505997
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Transcriptomic Changes in the Hypothalamic-Neurohypophysial System after 24 h of Furosemide-Induced Sodium Depletion

Abstract: Background/Aims: Furosemide is a loop diuretic widely used in clinical practice for the treatment of oedema and hypertension. The aim of this study was to determine physiological and molecular changes in the hypothalamic-neurohypophysial system as a consequence of furosemide-induced sodium depletion. Methods: Male rats were sodium depleted by acute furosemide injection (10 and 30 mg/kg) followed by access to low sodium diet and distilled water for 24 h. The renal and behavioural consequences were evaluated, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 56 publications
(96 reference statements)
5
13
0
Order By: Relevance
“…9B). RNA-seq has suggested that OPN3 is present in the supraoptic nucleus (Dutra et al, 2020), a region where we also found high OPN3-mCh expression. Additionally, Figure 10.…”
Section: Thalamus and Hypothalamussupporting
confidence: 71%
See 2 more Smart Citations
“…9B). RNA-seq has suggested that OPN3 is present in the supraoptic nucleus (Dutra et al, 2020), a region where we also found high OPN3-mCh expression. Additionally, Figure 10.…”
Section: Thalamus and Hypothalamussupporting
confidence: 71%
“…In the hypothalamus, OPN3 mRNA was initially identified in the PVH and medial preoptic area (MPA) by RNA-seq (Dutra et al, 2020), Western blotting, and immunostaining (Nissilä et al, 2012). We confirmed that OPN3-mCh was expressed in the MPA and highly expressed in the PVH (Fig.…”
Section: Thalamus and Hypothalamussupporting
confidence: 67%
See 1 more Smart Citation
“…Conversely, the use of loop diuretics as a cause for sodium depletion is highly likely, as the prescribed furosemide dosage was higher among hyponatremic CRS patients in comparison to non-hyponatremic ones. In addition to sodium depletion, loop diuretics induce a hypovolemia-triggered, appropriate AVP activation [30].…”
Section: Hypovolemia As a Main Cause Of Hyponatremia In Hospitalized mentioning
confidence: 99%
“…The latter was excluded for the patients of the current study. Conversely, the use of loop diuretics as a cause for sodium depletion is highly likely 28 , as the prescribed furosemide dosage was higher among hyponatremic CRS patients in comparison to non-hyponatremic ones. In addition to sodium depletion, loop diuretics induce a hypovolemiatriggered, appropriate AVP activitation 28 .…”
Section: Hypovolemia As a Main Cause Of Hyponatremia In Hospitalized mentioning
confidence: 99%